Manajemen Perlindungan Hukum Kegiatan Penghijauan Dan Gotong Royong Mahasiswa Pencinta Alam Gunung Hitam STIE IBMI Medan - Bayu Teta; Siti Junaida Hasibuan (Jurnal Pengabdian Pada Masyarakat METHABDI, 2025)
The reforestation and community service activities at STIE IBMI Medan aim to enhance the academic community's awareness of environmental conservation, strengthen solidarity among students, lecturers, and the surrounding community, and provide practical knowledge about sustainable planting techniques. This program also integrates legal aspects to create synergy between environmental awareness and regulatory compliance, with the goal of establishing an inspiring eco-friendly campus model. The results of the activity demonstrated success in creating a greener and healthier campus environment, while also raising awareness among students and the community about the importance of environmental preservation. Through community collaboration, social relationships among the academic community and the surrounding society were significantly strengthened. The active participation of the Gunung Hitam Nature Enthusiasts Association was a key factor in the program's success, culminating in the planting and arrangement of plants in various strategic campus locations. This success brings STIE IBMI Medan closer to becoming a role model for eco-friendly educational institutions.